1997
DOI: 10.1159/000227688
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Study of Flutamide in Ovarian Cancer

Abstract: A phase II study of flutamide was conducted in 24 patients with stage III and IV ovarian cancer who failed chemotherapy and who had measurable disease. Flutamide was administered at a dose of 100 mg three times daily continuously until evidence of progression. Partial response observed in 1 of the 23 evaluable patients (4.3%) lasted 3 months. Two patients had stable disease (8.7%) for 7 and 8 months. The remaining 20 patients had progression of disease within 3 months. Toxicity was mild.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Furthermore, in a nested case-control study, prediagnostic androgen levels were higher in ovarian cancer cases than in controls (4). In phase 2 clinical trials of antiandrogens as a treatment for ovarian cancer, investigators observed that antiandrogens reduced the tumor burden or stabilized the progression of ovarian cancer in some women who had previously failed at least one chemotherapy (5,6). Although data from animal models and cell lines have been less consistent (7)(8)(9), showing both stimulation and inhibition of ovarian cell growth with androgen administration, the epidemiologic and clinical data seem to suggest a role for androgens in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a nested case-control study, prediagnostic androgen levels were higher in ovarian cancer cases than in controls (4). In phase 2 clinical trials of antiandrogens as a treatment for ovarian cancer, investigators observed that antiandrogens reduced the tumor burden or stabilized the progression of ovarian cancer in some women who had previously failed at least one chemotherapy (5,6). Although data from animal models and cell lines have been less consistent (7)(8)(9), showing both stimulation and inhibition of ovarian cell growth with androgen administration, the epidemiologic and clinical data seem to suggest a role for androgens in ovarian cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity profile of Flutamide, unlike retinoic acids, in human studies is reportedly favorable (25). Moreover, since Flutamide works at the prostate level 11 and consequently, testosterone blood levels are not reduced, libido and potency are maintained (26).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not yet clear whether patients with lowgrade ovarian tumors do represent a group more likely to benefit from treatments affecting the GnRH axis. The AR inhibitor flutamide was assessed in two, nonrandomized phase II trials [65,66]. Tumolo and colleagues reported a response rate (RR) of 6.3% (n ϭ 2) and SD rate of 28% (n ϭ 9) with a median SD duration of 24 weeks [65].…”
Section: Clinical Trials With Compounds Affecting the Androgen Axismentioning
confidence: 99%
“…All patients were heavily pretreated (median of two chemotherapy lines) and had documented disease progression on screening. In a second trial by Vasillomanolakis and colleagues, 24 patients who progressed on chemotherapy received a low dose (100 mg three times a day) of flutamide [66]. One patient responded to the treatment (4.3%) and two patients had SD for Ն7 months.…”
Section: Clinical Trials With Compounds Affecting the Androgen Axismentioning
confidence: 99%